Handbook of Simulation Optimization - Fu, Michael C. (Springer New York, 2014)
The Handbook of Simulation Optimization presents an overview of the state of the art of simulation optimization, providing a survey of the most well-established approaches for optimizing stochastic simulation models and a sampling of recent research advances in theory and methodology. Leading contributors cover such topics as discrete optimization via simulation, ranking and selection, efficient simulation budget allocation, random search methods, response surface methodology, stochastic gradient estimation, stochastic approximation, sample average approximation, stochastic constraints, variance reduction techniques, model-based stochastic search methods and Markov decision processes. This single volume should serve as a reference for those already in the field and as a means for those new to the field for understanding and applying the main approaches. The intended audience includes researchers, practitioners and graduate students in the business/engineering fields of operations research, management science, operations management and stochastic control, as well as in economics/finance and computer science
Description based on publisher supplied metadata and other sources
Keywords: Discrete-time systems -- Handbooks, manuals, etc; Simulation methods -- Handbooks, manuals, etc; Stochastische Optimierung; Markov-Entscheidungsprozess